An integrated Multi-Criteria Decision Making and Multi-Choice Conic Goal Programming approach for customer evaluation and manager assignment - Dagistanli, Hakan Ayhan; Üstün, Özden (Decision analytics journal, 2023)
Companies adopt a customer-centric approach to maintain their competitive position or dominate the market. In this context, managers are pivotal in navigating the competitive markets in accomplishing these goals. Setting targets and conducting performance evaluations are vital for managers’ long-term success. This study aims to optimise customer evaluation and manager assignment in the defence industry. An integrated approach utilising the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is employed to conduct a comprehensive market analysis and conduct this evaluation. A bi-objective integer programming model is formulated to maximise​ total integrated scores and potential returns. The efficient number of visits is determined by combining Multi-Criteria Decision Making (MCDM) and Multi-Choice Conic Goal Programming (MCCGP). This study offers an objective alternative to traditional survey-based evaluations by proposing a novel decision support system for Goal-Based Performance Appraisals (GBPA) of managers. The proposed approach yields performance values that are considerably more reliable than questionnaire results. Moreover, the proposed decision support system can effectively benefit employees across diverse sectors, extending beyond the confines of the defence industry. •Propose an integrated approach for customer evaluation and manager assignment in the defence industry.•Use Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for market analysis.•Develop a bi-objective integer programming model to evaluate customer returns.•Propose a multi-choice conic goal programming to obtain efficient solutions considering goal intervals and weights.•Perform goal-based performance appraisals of managers objectively.